Enhanced Hemocompatibility of Silver Nanoparticles Using the Photocatalytic Properties of Titanium Dioxide - Chen, Xiao; Dai, Sheng; Liu, Luying; Liu, Peng; Ye, Peng; Liao, Yuzhen; Zhao, Ansha; Yang, Ping; Huang, Nan; Chen, Jiang (Frontiers in Bioengineering and Biotechnology, 2022)
Silver nanoparticles (AgNPs) are widely used because of their excellent antimicrobial properties. However, the poor hemocompatibility limits the application of AgNPs in blood contact materials. General approaches to improve the hemocompatibility of AgNPs-containing surfaces are to construct barrier layers or co-immobilize anticoagulant biomolecules. But such modification strategies are often cumbersome to prepare and have limited applications. Therefore, this study proposes a simple UV-photo-functionalization strategy to improve the hemocompatibility of AgNPs. We loaded AgNPs onto TiO2 nanoparticles to form a composite nanoparticles (Ag@TiO2NPs). Then, UV treatment was performed to the Ag@TiO2NPs, utilizing the diffusible photo-induced anticoagulant properties of TiO2 nanoparticles to enhance the hemocompatibility of AgNPs. After being deposited onto the PU surface, the photo-functionalized Ag@TiO2NPs coating showed excellent antibacterial properties against both Gram-positive/Gram-negative bacteria. Besides, In vitro and ex-vivo experiments demonstrated that the photo-functionalized Ag@TiO2NPs coating had desirable hemocompatibility. This modification strategy can provide a new solution idea to improve the hemocompatibility of metal nanoparticles.